Relationship Between Self-Efficacy and Independence in Performing Activities of Daily Living Among the Elderly - Fadilla, Fany; Sianturi, Sondang Ratnauli (Side: Scientific Development Journal, 2026)
The rapid growth of the elderly population in Indonesia has increased the demand for long-term care and support, particularly in institutional settings. Maintaining independence in activities of daily living is a critical determinant of quality of life among older adults. Psychological factors, especially self-efficacy, play a pivotal role in sustaining functional independence. This study aimed to examine the relationship between self-efficacy and the level of independence in performing ADL among older adults residing in a social care institution. A quantitative, descriptive-correlational study with a cross-sectional design was conducted among 66 older adults living at PSTW Budi Mulia 2 Cengkareng,Jakarta. Participants were selected using purposive sampling. Self-efficacy was measured using the Indonesian version of the General Self-Efficacy Scale, while ADL independence was assessed using the Barthel Index. Data were analysed using the Chi-square test with a significance level of p< 0.05. The majority of participants demonstrated high self-efficacy (95.4%) and were independent in ADL (96.9%). A statistically significant association was found between self-efficacy and ADL independence (p < 0.05). Older adults with high self-efficacy were significantly more likely to perform daily activities independently than those with low self-efficacy. Self-efficacy is significantly associated with functional independence among institutionalized older adults. Strengthening self-efficacy through structured physical, psychological, and social interventions may contributed to sustaining independence and improving quality of life in elderly care institutions.